Green and efficient purification method of high-purity quartz sand

Through the green process of mechanical-chemical synergistic pretreatment, microwave-assisted deep impurity removal and directional adsorption purification, the problems of environmental protection, economy and purity in the purification process of high-purity quartz sand in the existing technology are solved, and efficient and environmentally friendly high-purity quartz sand production is achieved.

CN120793938APending Publication Date: 2025-10-17HENAN XINXIN SILICON-BASED NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511047648.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing high-purity quartz sand purification technology is difficult to achieve a balance in terms of environmental protection, economy and purity. The chemical acid leaching method is seriously polluting, the physical sorting efficiency is low, the biological leaching method has a long cycle, and the high-temperature chlorination method has high energy consumption and risks.

Method used

A green and efficient process of mechanical-chemical synergistic pretreatment, microwave-assisted deep impurity removal, directional adsorption purification, and ultrapure water washing and drying is adopted. Composite organic acid is used instead of hydrofluoric acid, combined with microwave heating and thiol-modified silica gel nanoparticle adsorption to achieve efficient removal of impurities.

Benefits of technology

It reduces wastewater treatment costs and energy consumption, improves the purity and purification efficiency of quartz sand, meets the needs of high-end industries, and realizes environmentally friendly and safe production of high-purity quartz sand.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120793938A_ABST
    Figure CN120793938A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of quartz sand purification, in particular to a green and efficient purification method of high-purity quartz sand, which comprises four steps of mechanical-chemical synergistic pretreatment, microwave-assisted deep impurity removal, directional adsorption purification and ultrapure water washing and drying. The traditional hydrofluoric acid process is replaced by the composite organic acid, so that the COD (Chemical Oxygen Demand) of the wastewater is reduced by more than 90%, the waste liquid treatment cost is greatly reduced, meanwhile, the problem of corrosion of strong acid to equipment is avoided, the energy consumption is reduced by 40% through the microwave process, and no chlorine is discharged, so that the production process is more environment-friendly and safer, the content of Al2O3 is reduced from 500ppm to 8ppm, and the production cost is reduced. Compared with the prior art, the method provided by the invention has the advantages that the content of Fe2O3 is reduced from 200ppm to 3ppm, meanwhile, the inclusion removal rate is greater than 99.5%, and the purity of SiO2 reaches 99.995%, so that the problem that micron-sized inclusion impurities are difficult to deeply remove is solved, and the purification efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of quartz sand purification, and particularly relates to a green and efficient purification method of high-purity quartz sand. BACKGROUND

[0002] As a key basic material for high-end industries such as semiconductors, photovoltaics and optical fiber communications, the purity of high-purity quartz sand directly affects the performance of the final product. Currently, chemical acid leaching, physical sorting and high-temperature chlorination are mainly used in industrial production. These methods have formed a relatively mature technical system in long-term application.

[0003] Among them, the chemical acid leaching method generally relies on strong corrosive reagents such as hydrofluoric acid, which not only produces a large amount of fluorine-containing wastewater, but also causes serious corrosion of equipment, and has poor environmental protection; the physical sorting technology has limited removal efficiency for micron-sized inclusion impurities, and it is difficult to meet the purity requirement of more than 99.99%; the high-temperature chlorination method has good purification effect, but has high energy consumption and chlorine leakage risk; and the emerging bioleaching method faces the problems of long cycle and poor stability of bacterial strains, which restricts the application of high-purity quartz sand in higher-end fields.

[0004] Therefore, in view of the above problems, the present application provides a green and efficient purification method of high-purity quartz sand, which realizes efficient removal of impurities while reducing energy consumption and pollution through mechanical-chemical synergistic pretreatment, microwave-assisted deep impurity removal, directional adsorption purification and ultrapure water washing and drying. SUMMARY

[0005] In order to overcome the problem that the prior art cannot balance environmental protection, economy and ultra-high purity requirements, the present application provides a green and efficient purification method of high-purity quartz sand.

[0006] The technical scheme of the present application is as follows: a green and efficient purification method of high-purity quartz sand, comprising: S1, mechanical-chemical synergistic pretreatment; S2, microwave-assisted deep impurity removal; S3, directional adsorption purification; S4, ultrapure water washing and drying.

[0007] As a preferred, the mechanical treatment of step S1 comprises: firstly crushing the quartz raw ore through a jaw crusher, and then finely crushing to 100-200 mesh particle size using a high-pressure pulse crusher, which effectively dissociates the inclusion impurities from the quartz matrix by using the selective crushing characteristics of high-pressure pulse.

[0008] Preferably, the chemical treatment in step S1 includes: placing the crushed quartz sand into a reactor, adding a composite organic acid solution composed of citric acid and oxalic acid, stirring and leaching at a temperature range of 60-80°C for 2-4 hours, maintaining a constant temperature during the reaction and monitoring the acidity change with a pH meter, and achieving solid-liquid separation by vacuum filtration after the reaction. The obtained solid material is washed with deionized water until neutral and then enters the next process.

[0009] Preferably, step S2 comprises: uniformly mixing the pretreated quartz sand and ammonium chloride in a mixer at a mass ratio of 10:1 for 30 minutes.

[0010] Preferably, step S2 further comprises: charging the mixed material into a quartz crucible and placing it in a microwave reactor, introducing nitrogen to replace the air in the reaction cavity, starting the microwave heating system, heating the material to 600-800°C, and maintaining it for 30-60 minutes, during which the material temperature is monitored in real time by an infrared thermometer, and the microwave power is controlled within the range of 5-10kW. During the reaction, impurity elements such as aluminum and iron are converted into volatile chlorides and escape, and the generated volatile chlorides are collected by the exhaust gas treatment system. After the reaction is completed, the material is naturally cooled to room temperature, and the material is taken out and sieved to remove the unreacted ammonium chloride residue.

[0011] Preferably, the directional adsorption purification includes: placing microwave-treated quartz sand into an adsorption tank, adding a functionalized adsorption liquid containing thiol-modified silica gel nanoparticles, using an acid-base regulator to accurately control the pH value of the system within the range of 3-4, and starting a mechanical stirrer to stir at a speed of 150-200 rpm.

[0012] Preferably, the directional adsorption purification further comprises: turning on an ultrasonic generator, setting the frequency to 40 kHz, continuing the reaction for 1-2 hours under the dual action of ultrasonic cavitation effect and mechanical stirring, and standing for 30 minutes after the reaction is completed.

[0013] Preferably, the ultrapure water washing and drying includes: transferring the adsorption-purified quartz sand to a washing tank, performing countercurrent washing with 18.2 MΩ·cm ultrapure water, controlling the water-sand ratio to 4:1, maintaining the washing temperature at 25-30°C, monitoring the washing water quality with an online conductivity meter, and stopping washing when the outlet water pH value reaches 6.5-7.5 and the conductivity is less than 0.1 μS / cm.

[0014] Preferably, the ultrapure water washing and drying further comprises: loading the washed quartz sand into a centrifuge, dehydrating at a speed of 3000-4000 rpm for 10-15 minutes, and then evenly laying the material on a tray of a vacuum drying oven, setting the drying temperature to 120° C. and the drying time to 4-6 hours, and finally obtaining a high-purity quartz sand product with a water content of less than 0.1%.

[0015] As preferred, the added composite organic acid solution consists of citric acid and oxalic acid is 5-10%.

[0016] Advantages of the present application: 1. The present application uses composite organic acid to replace the traditional hydrofluoric acid process, which reduces the COD of wastewater by more than 90%, greatly reduces the treatment cost of waste liquid, and avoids the corrosion problem of strong acid to equipment, while the microwave process reduces the energy consumption by 40%, and there is no chlorine gas emission, so that the production process is more environmentally friendly and safe.

[0017] 2. The content of Al2O3 is reduced from 500ppm to 8ppm, and the content of Fe2O3 is reduced from 200ppm to 3ppm, while the inclusion removal rate is >99.5%, and the purity of SiO2 is 99.995%, solving the problem of difficult deep removal of micron-sized inclusion impurities, greatly improving the purification efficiency.

[0018] 3. The comprehensive cost of the present application is reduced by 35% compared with the traditional acid leaching method, the microwave process shortens the treatment time by 50%, and the adsorbent can be recycled more than 5 times, thereby reducing the purification cost.

[0019] 4. The present application has no super-high temperature / high pressure equipment throughout the process, which is suitable for modification of existing production lines, thereby reducing energy consumption (target <800℃), and avoiding the defects of high-temperature chlorination process. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 The working flowchart of the present application is shown. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.

[0022] Please refer to Figure 1 The present application provides an embodiment: a green and efficient purification method for high-purity quartz sand, comprising: S1, mechanical-chemical synergistic pretreatment; S2, microwave-assisted deep impurity removal; S3, directional adsorption purification; S4, ultrapure water washing and drying.

[0023] Preferably, the mechanical treatment of step S1 comprises: firstly, rough crushing the quartz ore by a jaw crusher, and then, fine crushing the quartz ore to a particle size of 100-200 mesh by using a high-pressure pulse crusher to effectively dissociate the impurity inclusions from the quartz matrix by virtue of the selective crushing characteristics of high-pressure pulses.

[0024] The chemical treatment of step S1 comprises: placing the crushed quartz sand into a reaction kettle, adding a composite organic acid solution composed of citric acid and oxalic acid, stirring and leaching at a temperature of 60-80°C for 2-4 hours, maintaining constant temperature during the reaction and monitoring the change in acidity by a pH meter, and after the reaction, achieving solid-liquid separation by vacuum filtration, and then washing the obtained solid material with deionized water until neutral for the next process.

[0025] The step S2 comprises: uniformly mixing the pretreated quartz sand and ammonium chloride in a mass ratio of 10:1 in a mixer for 30 minutes.

[0026] The step S2 further comprises: loading the mixed material into a quartz crucible and placing it in a microwave reactor, replacing the air in the reaction cavity with nitrogen, starting the microwave heating system, heating the material to 600-800°C for 30-60 minutes, monitoring the material temperature in real time by an infrared temperature meter during the heating, controlling the microwave power in the range of 5-10 kW, converting the impurity elements such as aluminum and iron into volatile chlorides and escaping during the reaction, collecting the generated volatile chlorides by the tail gas treatment system, naturally cooling the material to room temperature after the reaction, and removing the unreacted ammonium chloride residue by sieving.

[0027] The directional adsorption purification comprises: placing the microwave-treated quartz sand into an adsorption tank, adding a functionalized adsorption solution containing thiol-modified silica gel nanoparticles, accurately controlling the pH value of the system in the range of 3-4 by using an acid-base regulator, and starting a mechanical stirrer to stir at a speed of 150-200 rpm.

[0028] The directional adsorption purification further comprises: turning on an ultrasonic generator and setting the frequency to 40 kHz, continuously reacting for 1-2 hours under the dual action of ultrasonic cavitation effect and mechanical stirring, and standing for 30 minutes after the reaction.

[0029] The ultrapure water washing and drying comprises: transferring the adsorption-purified quartz sand to a washing tank, using 18.2MΩ·cm ultrapure water for countercurrent washing, controlling the water / sand ratio to be 4:1, maintaining the washing temperature at 25-30°C, and monitoring the washing water quality by an online conductivity meter, and stopping the washing when the effluent pH value reaches 6.5-7.5 and the conductivity is less than 0.1μS / cm.

[0030] The washing and drying of the ultra-pure water further comprises: loading the washed quartz sand into a centrifuge, dehydrating at a speed of 3000-4000 rpm for 10-15 minutes, then evenly laying the material on the tray of a vacuum drying oven, setting the drying temperature to 120℃, and drying for 4-6 hours to obtain the high-purity quartz sand product with a water content of less than 0.1%.

[0031] The added composite organic acid solution consists of citric acid and oxalic acid, and the concentration is 5-10%.

[0032] Further, the high-purity quartz sand green and efficient purification method provided by the application comprises four key process stages, and the implementation modes of each stage will be described in detail below in combination with specific embodiments.

[0033] The first stage is mechanical-chemical synergistic pretreatment, and in the specific implementation, vein quartz with a SiO2 content of 99.2% is used as the raw material. First, the raw material is coarsely crushed to a particle size of 5-10 mm by a jaw crusher, and then finely crushed by a high-voltage pulse crusher at a voltage of 50 kV and a pulse frequency of 100 times / s, with the final particle size controlled to be 150 mesh. This process can effectively dissociate the combination interface of quartz and impurity inclusions. The crushed quartz sand is then put into a reaction kettle with stirring and heating functions, and a pre-configured composite organic acid solution (8% citric acid + 2% oxalic acid) is added according to a liquid-solid ratio of 3:1. The temperature is raised to 70℃, and the stirring speed is set to 250 rpm for continuous stirring for 3 hours. During the reaction process, the pH automatic control system is used to maintain the pH value of the system in the range of 2.5-3.0. After the reaction is completed, solid-liquid separation is performed by using a plate and frame filter press, and the filter cake is washed with deionized water until it is neutral. The detection shows that the removal rate of surface free metal impurities at this time is more than 85%, which lays a good foundation for subsequent treatment.

[0034] The second stage implements a microwave-assisted deep impurity removal process. The pretreated quartz sand is mixed with analytical pure ammonium chloride in a V-type mixer at a mass ratio of 10:1 for 30 minutes. The mixture is loaded into a high-purity quartz crucible and placed in a multi-mode cavity microwave reactor. High-purity nitrogen gas is first introduced at a flow rate of 10 L / min to replace the air in the cavity for 10 minutes. Then the microwave heating system is turned on, the temperature rising rate is controlled to be 15℃ / min, the target temperature is set to 750℃, the microwave power is 8 kW, and the temperature is kept for 45 minutes after reaching the target temperature. During this period, the material temperature is monitored in real time by an infrared temperature detector, and the microwave power is automatically adjusted to keep the temperature fluctuation within ±5℃. During the reaction process, impurity elements such as aluminum and iron are converted into volatile chlorides such as AlCl3 and FeCl3, which are collected by a condensation recovery system. After the reaction is completed, the microwave power is turned off, and nitrogen gas is continuously introduced to protect the material until it cools down to below 80℃ and is discharged. The unreacted ammonium chloride residue is removed by screening. ICP detection shows that the Al2O3 content is reduced from 500 ppm to 50 ppm, and the Fe2O3 content is reduced from 200 ppm to 20 ppm, indicating a significant impurity removal effect.

[0035] The third stage implements a directional adsorption purification process, the quartz sand after microwave treatment is transferred to an adsorption reaction tank with an ultrasonic device, 2wt% thiol modified silica gel nanoparticles are added into the functionalized adsorption liquid in a liquid-solid ratio of 5:1, dilute hydrochloric acid is used to adjust the pH to 3.5, a double-layer propelling stirrer is started to stir at a rotating speed of 180 rpm, at the same time, the ultrasonic system is started, the frequency is set to 40 kHz, and the power density is 0.8 W / cm², under the synergistic action of mechanical stirring and ultrasonic cavitation, the reaction is carried out for 1.5 hours, after the reaction is completed, the adsorbent is naturally settled for 30 minutes, the supernatant is filtered through a 0.45 μm microporous filter membrane and then recycled, the filter cake is separated by a plate and frame filter press, and then washed with ultrapure water in a countercurrent manner for three times, when the conductivity of the washing liquid is less than 5 μS / cm, the washing is stopped, at this time, the content of residual heavy metals in the quartz sand is further reduced, the content of Al is reduced to 8 ppm, and the content of Fe is reduced to 3 ppm, and the semiconductor grade purity requirement is reached.

[0036] The fourth stage implements an ultrapure water washing and drying process, the quartz sand after adsorption purification is loaded into a washing column made of polypropylene, and 18.2MΩ·cm ultrapure water is used for dynamic countercurrent washing, the water temperature is controlled to be 25℃, and the flow rate is controlled to be 2BV / h, the water quality is monitored in real time through an online pH meter and a conductivity meter, when the pH value is stable at 6.8-7.2 and the conductivity is less than or equal to 0.1 μS / cm, the washing is stopped, the wet sand after washing is loaded into a high-speed centrifuge to be dehydrated at a rotating speed of 3500 rpm for 12 minutes, so that the water content is reduced to less than 15%, then the material is evenly laid on multiple trays in a vacuum drying oven, the drying temperature is set to be 120℃, the material is turned over every 1 hour during the drying process to ensure uniform heating, after 5 hours, the sampling detection shows that the water content is less than or equal to 0.05%, finally, the high-purity quartz sand product obtained has a SiO2 purity of 99.996% through GDMS analysis, the content of key impurity elements is Al 7 ppm, Fe 2 ppm and Ti 4 ppm, all indexes are better than the industry standard, and the high-end semiconductor manufacturing demand is fully met.

[0037] Further, the traditional acid leaching (10% HF+5% HCl) is used for purification, finally, the SiO2 purity is 99.91%, the content of Al is 45 ppm, the content of Fe is 18 ppm, and fluorine-containing wastewater is generated.

[0038] It can be concluded from the above that the environmental protection and purification efficiency of the application are greatly improved.

[0039] Further, the application provides an embodiment, the raw material uses the vein quartz mine in Brazil, the SiO2 content is 99.3%, the main impurity is Al2O3 (480ppm), Fe2O3 (210ppm), the ore is coarsely crushed after the jaw crusher in the pretreatment stage, is pulverized to 120 mesh using high pressure pulse crusher, 500g broken material is taken with 5L complex organic acid solution (7% citric acid+3% oxalic acid) is stirred and reacted at 75 DEG C for 3.5 hours, after solid-liquid separation, it is measured that Al2O3 reduces to 120ppm, the microwave impurity removal stage is mixed with 50g NH4Cl and is loaded into the quartz crucible, is treated at 700 DEG C for 50 minutes in the microwave reactor, after treatment, Al2O3 reduces to 25ppm, the adsorption purification stage uses 1.5wt% mercapto silica gel adsorption liquid (pH3.2), is treated for 1.2 hours under the assistance of ultrasonic, and the final product is detected by ICP-MS and shows that the SiO2 purity is 99.994%, Al6ppm, Fe2ppm.

[0040] Further, the application provides an embodiment, the quartz sand produced in Jiangsu is selected, the initial SiO2 purity is 99.1%, contains Al2O3 (520ppm), Ti (85ppm), the pretreatment adopts two-stage crushing: first jaw breaking to 8mm, then high pressure pulse crushing to 180 mesh, 1kg raw material is taken with 8L complex acid (9% citric acid+1% oxalic acid) and is reacted at 65 DEG C for 4 hours, and the Ti content reduces to 40ppm.Microwave stage is mixed with NH4Cl at a ratio of 12:1, is treated at 780 DEG C for 35 minutes, and Al2O3 reduces to 15ppm, the adsorption stage uses 2wt% mercapto silica gel (pH3.8) and is treated for 2 hours under the assistance of ultrasonic, and the final product Ti content reduces to 3ppm, and the SiO2 purity is 99.997%, especially suitable for photovoltaic silicon wafer application.

[0041] Through the above steps, the complex organic acid is used instead of the traditional hydrofluoric acid process, the wastewater COD is reduced by more than 90%, the waste liquid treatment cost is greatly reduced, the corrosion problem of strong acid to equipment is avoided, the microwave process reduces the energy consumption by 40%, and there is no chlorine gas emission, so that the production process is more environmentally friendly and safe, the content of Al2O3 is reduced from 500ppm to 8ppm, the content of Fe2O3 is reduced from 200ppm to 3ppm, the inclusion removal rate is greater than 99.5%, the SiO2 purity reaches 99.995%, the problem that micron-sized inclusion impurities are difficult to remove deeply is solved, and the purification efficiency is greatly improved, so as to solve the problem that the prior art cannot consider environmental protection, economy and ultra-high purity demand.

Claims

1. A green and efficient purification method for high-purity quartz sand, characterized in that: Includes: S1, mechanical-chemical synergistic pretreatment; S2, microwave-assisted deep impurity removal; S3, directed adsorption purification; S4, ultrapure water washing and drying.

2. A green and efficient purification method for high-purity quartz sand according to claim 1, characterized in that, The mechanical treatment in step S1 includes: firstly, coarsely crushing the quartz ore by a jaw crusher, and then finely crushing it to a particle size of 100-200 mesh using a high-pressure pulse crusher, and utilizing the selective crushing characteristics of the high-pressure pulse to effectively dissociate the impurity inclusions from the quartz matrix.

3. A green and efficient purification method for high-purity quartz sand according to claim 3, characterized in that, The chemical treatment in step S1 comprises: placing the crushed quartz sand into a reactor, adding a composite organic acid solution composed of citric acid and oxalic acid, stirring and leaching at a temperature range of 60-80° C. for 2-4 hours, maintaining a constant temperature during the reaction and monitoring the acidity change with a pH meter, and performing solid-liquid separation by vacuum filtration after the reaction. The obtained solid material is washed with deionized water until neutral before entering the next process.

4. A green and efficient purification method for high-purity quartz sand according to claim 1, characterized in that, The step S2 comprises: uniformly mixing the pretreated quartz sand and ammonium chloride in a mixer at a mass ratio of 10:1 for 30 minutes.

5. A green and efficient purification method for high-purity quartz sand according to claim 4, characterized in that, The step S2 further includes: charging the mixed material into a quartz crucible and placing it in a microwave reactor, introducing nitrogen to replace the air in the reaction chamber, starting a microwave heating system, heating the material to 600-800° C., and maintaining the temperature for 30-60 minutes, during which the material temperature is monitored in real time by an infrared thermometer, and the microwave power is controlled within the range of 5-10 kW. During the reaction, impurity elements such as aluminum and iron are converted into volatile chlorides and escape, and the generated volatile chlorides are collected by an exhaust gas treatment system. After the reaction is completed, the material is naturally cooled to room temperature, and the material is removed and sieved to remove unreacted ammonium chloride residue.

6. A green and efficient purification method for high-purity quartz sand according to claim 1, characterized in that, The directional adsorption purification includes: placing microwave-treated quartz sand into an adsorption tank, adding a functionalized adsorption liquid containing thiol-modified silica gel nanoparticles, using an acid-base regulator to accurately control the pH value of the system within the range of 3-4, and starting a mechanical stirrer to stir at a speed of 150-200 rpm.

7. A green and efficient purification method for high-purity quartz sand according to claim 6, characterized in that, The directional adsorption purification further includes: turning on an ultrasonic generator, setting the frequency to 40 kHz, continuing the reaction for 1-2 hours under the dual effects of ultrasonic cavitation effect and mechanical stirring, and standing for 30 minutes after the reaction is completed.

8. A green and efficient purification method for high-purity quartz sand according to claim 1, characterized in that: The ultrapure water washing and drying comprises: transferring the adsorbed purified quartz sand into a washing tank, performing countercurrent washing with 18.2 MΩ·cm ultrapure water, controlling the water-to-sand ratio to 4:1, maintaining the washing temperature at 25-30°C, monitoring the washing water quality with an online conductivity meter, and stopping washing when the outlet water pH value reaches 6.5-7.5 and the conductivity is less than 0.1 μS / cm.

9. The green and efficient purification method for high-purity quartz sand according to claim 8, characterized in that: The ultrapure water washing and drying also includes: loading the washed quartz sand into a centrifuge, dehydrating it at a speed of 3000-4000 rpm for 10-15 minutes, and then evenly laying the material on a tray of a vacuum drying oven, setting the drying temperature to 120°C and the drying time to 4-6 hours, and finally obtaining a high-purity quartz sand product with a moisture content of less than 0.1%.

10. The green and efficient purification method for high-purity quartz sand according to claim 3, characterized in that: The added composite organic acid solution consisting of citric acid and oxalic acid is 5-10%.

Citation Information

Cited By

  • Quartz sand gas-liquid inclusion flash burst method and device

    CN121470493A